Morfologia em alta resolução espacial de estrelas de tipo Mira e R Corenae Borealis - Leão, Izan de Castro (2009)
Mira and R Coronae Borealis (R CrB) variable stars are evolved objects surrounded by circumstellar envelopes (CSE) composed of the ejected stellar material. We present a detailed high-spatial resolution morfological study of the CSE of three stars: IRC+10216, the closest and more studied Carbon-Rich Mira; o Ceti, the prototype of the Mira class; and RY Sagitarii (RY Sgr), the brightest R CrB variable of the south hemisphere. JHKL near-infrared adaptive optics images of IRC+10216 with high dynamic range and Vband images with high angular resolution and high depth, collected with the VLT/NACO and VLT/FORS1 instruments, were analyzed. NACO images of o Ceti were also analyzed. Interferometric observations of RY Sgr collected with the VLTI/MIDI instrument allowed us to explore its CSE innermost regions (»20 40 mas). The CSE of IRC+10216 exhibit, in near-infrared, clumps with more complex relative displacements than proposed in previous studies. In V-band, the majority of the non-concentric shells, located in the outer CSE layers, seem to be composed of thinner elongated shells. In a global view, the morphological connection between the shells and the bipolar core of the nebulae, located in the outer layers, together with the clumps, located in the innermost regions, has a difficult interpretation. In the CSE of o Ceti, preliminar results would be indicating the presence of possible clumps. In the innermost regions (.110 UA) of the CSE of RY Sgr, two clouds were detected in different epochs, embedded in a variable gaussian envelope. Based on a rigorous verification, the first cloud was located at »100 R¤ (or »30 AU) from the centre, toward the east-north-east direction (modulo 180o) and the second one was almost at a perpendicular direction, having aproximately 2£ the distance of the first cloud. This study introduces new constraints to the mass-loss history of these kind of variables and to the morphology of their innermost CSE regions